Examining the Factor of Social Media Activities and Relationships of Cyberbullying Behaviour in Generation Z Indonesia - Umar, Nur Fadhilah; Pandang, Abdullah; Syahril, M. Fiqri; Rafli, Muhammad (Bulletin of Counseling and Psychotherapy, 2024)
This study focuses on analyzing factors that are significant to the occurrence of cyberbullying cases and identifying aspects of cyberbullying that have a significant influence on cyberbullying behavior in generation Z in Indonesia. The research method used is quantitative. The dependent variable in this study is cyberbullying and the independent variable is social media. The population of this study consisted of students from three provinces in Sulawesi, namely South Sulawesi, West Sulawesi and Central Sulawesi. Samples were taken from the third province of Sulawesi as many as 389 students using the proportional stratified random sampling method. Data analysis used the prerequisite test analysis approach through the data normality test and data linearity test using the ANOVA statistical technique using the JASP statistical application. The results of the study show that the factors that have a significant influence on cyberbullying behavior in generation Z students are the intensity of comments on social media. The intensity factor of using social media and the type of social media have no effect on cyberbullying behavior. Aspects of verbal written bullying and social exclusion have no significant effect on cyberbullying. The visual aspect of sexual bullying on cyberbullying behavior in terms of the intensity factor of giving comments on social media has a strong significant difference. Therefore it can be concluded that visually sexual negative comments are related to the level of cyberbullying behavior in Generation Z in Sulawesi, Indonesia